Shifting the anthocyanins from light to shade: what roles do these pigments play? - Gaion, Lucas Aparecido; Galati, Valéria Cury [UNESP]; Cardoso, Ana Carolina Roque [UNESP]; Rossatto, Davi Rodrigo [UNESP]; Carvalho, Rogério Falleiros [UNESP] (Springer Nature, 2025)
It is well known that anthocyanins protect the photosynthetic apparatus from excessive light. However, under shading conditions, anthocyanins could competitively limit light absorption by chlorophylls. Therefore, the objective of this work was to verify if anthocyanins impair light absorption by chlorophylls in a shaded environment. For this purpose, two varieties of coleus (Solenostemon scutellarioides (L.) Codd) were used as a study model. One variety exhibited leaves accumulating anthocyanins, while the other did not accumulate anthocyanins. Plants were cultivated in two light conditions (shade and sun) for a period of thirty days. For the shade condition, the varieties remained under tree vegetation with PPFD of approximately 80 µmol m−2 s−1, while the PPFD under sunny conditions was 1300 µmol m−2 s−1. Pigment concentrations, including chlorophyll, carotenoids and anthocyanins, as well as leaf area, carbohydrate concentration, photosynthetic parameters, and leaf anatomy were evaluated. We observed that the anthocyanins affected the photosynthetic rate, maximum electron transport rate, maximum quantum efficiency and pigment concentration. However, the light factor was the key factor driving the greater growth of plants cultivated under sunlit condition, regardless of the variety, or the presence of anthocyanin accumulation. In shaded conditions, anthocyanins act as a filter, affecting the transmission of light to chlorophylls and altering both the quantity and quality of light reaching the chloroplasts. This interaction resulted in lower values for the evaluated photosynthetic parameters in variegated coleus grown under shade. However, the accumulation of anthocyanins in variegated plants did not hinder their development or carbohydrate production, suggesting that anthocyanins and chlorophylls can, to some extent, coexist and compete for available light without compromising overall plant function.
Keywords: Foliar anthocyanin; Light competition; Photomorphogenesis; Photoprotection; Solenostemon scutellarioides